Big Four or Big Fees? Latest Evidence of the Auditing Costs in the United States - Gazilas, Emmanouil Taxiarchis; Belesis, Nicholas D.; Kampouris, Christos G. (Golden Ratio of Auditing Research, 2025)
With an emphasis on the influence of Big Four auditors in the US between 2000 and 2024, this paper explores the factors that influence audit fees and associated non-audit fees. We examine trends in audit, tax-related, and miscellaneous fees using a dataset that includes 1,187 auditors and 13,822 distinct entities across 1,315 sectors. In order to determine if the Big Four auditors—Deloitte, PwC, EY, and KPMG—command a higher cost for their services, we examine how firm-specific factors like revenue, assets, book value, and earnings affect fee structures. This study looks at both linear and non-linear associations using advanced econometric methods, such as multiple regression analysis and non-parametric Wilcoxon rank-sum tests. It additionally incorporates interaction variables to account for differences between Big Four and non-Big Four auditors. The findings reveal that companies audited by Big Four auditors pay significantly more, which is symptomatic of their perceived market dominance and audit quality. While non-audit fees demonstrate clear trends impacted by auditor type, larger businesses with higher revenues and assets are also linked to higher rates.